Method of alkaline destruction as the way to stop methanogenic effluent's gasification - Tarasenko, Roman; Starzhinska, Lydmila; Polunkin, Ievgen; Shapovalov, Yevhenii (My University, 2019)
One of the main problems which limit the distribution of biogas plants is the fertilizer gasification [1]. This process provides a problem of the fertilizer storage. Previously additional fermentation was conducted to solve this problem. It is characterized by additional biogas output, but it suppose to build additional biogas reactor and this it still does not supply completed fermentation [2]. We propose the process of alkaline destructions to solve this problem. It can provide production synthesis gas and humate.
Keywords: кафедра харчової хімії; NMR spectroscopy; ЯМР спекторскопія; alkaline destructions; лужне руйнування; effluent; стоки; газифікація добрив; fertilizer gasification; гумати; humate